Creation accounts in Gen. 1 & 2: A Feminist Interpretation - Eyo, Ubong Ekpenyong (Center for Humanities and Innovation Studies, 2020)
It is the view of most people who claim the authoritative nature of the Bible that, women assigned secondary status in relation to men is ordained and supported in the Bible. Many have quoted different texts of the holy writ to support their culturally-biased position on issue of gender equality. Most often views in respect to gender issues are culturally-based and interpreted rather than divinely-based and interpreted. There is therefore the need to look back at Jesusâ€™ words, â€œBut at the beginning of creation God 'made them male and female.â€ (Matt 19:4; Mark 10:6 King James Version). The two accounts in the Book of Genesis by the Priestly and Yahwistic strands give a complimentary account of the creation of humankind (both male and female) in the image and likeness of God and their creation from a single stock ××“× who was not a male gender. At a cursory reading of the creation accounts, one will tend to see ×”××“× as the male gender, but looking at the Hebrew text more closely it will be noticed that the Hebrew words ××™×©×” and ××™×©were only introduced after the two genders have been separated. Note carefully that it was not ××™×© that was asked to tend the garden, who named the animals, was given instruction of what to eat or what not to eat, who fell into a deep sleep or whose ribs was used in the creation of ××™×©×” but it was ×”××“× . It was after the creation or â€˜separationâ€™ of ××™×©×” (woman â€“ the female ×”××“×) that the other part was called ××™×© (man â€“ the male ×”××“×) (see vv 23 & 24 King James Version). It will therefore not be right to speak of the creation of ××™×©×” out of ××™×©, because as at the time of the creation of the former, the later was not in existence as ××™×© To view these creation accounts with the sense of gender superiority (either male over female or vice versa) is to read the texts using lenses which have been obscured and tainted by patriarchal, matriarchal or cultural biases.